Influence of olive maturity and season on the quality of virgin olive oils from the area assigned to the protected designation of origin of “aceite de la alcarria” (Spain) - Pardo, José E.; Rabadán, Adrián; Suárez, Mariano; Tello, Jacinto; Zied, Diego C. [UNESP]; Álvarez-Ortí, Manuel (MDPI, 2021)
This work aimed to assess the influence of olive maturity and oil season on the potential quality of monovarietal virgin olive oils from the area assigned to the Protected Designation of Origin of “Aceite de la Alcarria” (Spain), analysing the regulated physicochemical quality and sensory parameters, the stability parameters and composition of fatty acids, sterols and triterpenic dialcohols. To complete the study, we also characterised the coupage olive oils made in the oil mills located in the PDO area (real quality). The main variety grown in La Alcarria is Castellana, whose oils are characterised by a high content of palmitic acid (14.27% with olives in veraison, 13.81% with ripe olives), a low content of linoleic acid (5.03% with olives in veraison, 5.98% with ripe olives) and a total phenol content higher than the rest of varieties grown in the area (between 350 and 500 mg of caffeic acid/kg depending on the season considered), which is reflected in higher oxidative stability values (induction time of 50.65 h at 100◦C). In addition, they have a sterol content below that established by the regulations (<1000 mg/kg). The olive oils produced using olives in veraison presented a lower level of acidity and peroxide index, more intense fruitiness, an absence of defects in all the samples and higher oxidative stability, compared to those produced using ripe olives, and thus early harvest of the olives is recommended. It was also found that the season affects the physicochemical composition of the oils, although these changes tend to be of little significance, with the characteristics of the variety being maintained, regardless of the harvesting season analysed. The coupage virgin olive oils produced in the mills registered under the PDO of Aceite de la Alcarria, representative of their real quality, showed, as expected, similar values to those observed in the monovarietal virgin olive oils produced using the Castellana variety, which is clearly predominant in the study area. The characterization of oils from local varieties allows one to obtain a greater variability in terms of the sensory notes of extra virgin olive oil.
Keywords: Alcarria; Maturation; Monovarietal extra virgin olive oil; Olive oil quality; Season